Giulio Rosso: São Paulo 2017 a presença italiana no mobiliário brasileiro - Bazanelli, Claudia Gobbi (2017)
Graduate thesis dedicated to studying the production of Italian artist Giulio Rosso, who immigrated to Brazil after World War II and he worked in the country as an interior architect. I try to find dialogues between the design of residential furniture made in Brazil in the first half of the twentieth century and the one practiced in Europe. In order to understand this production, I give an overview of the evolution of design from the nineteenth century to the 1940s. I begin with Europe, then dedicate a special space to Italy and, finally, I arrive at modernist Brazil